Dysregulated Serum Cytokine Production in Pediatric Patients with β-Thalassemia Major. (4th July 2022) - Zhang, Li; Bao, Li-Juan; Hong, Zheng-Dong; Yan, Mu-Xia; Zhang, Zhi-Hua; Li, Yan-Mei; Ye, Qian; Wang, Yi-Qian
Abstract: β-Thalassemia major (β-TM) is an inherited disorder of hemoglobin (Hb) production, which can cause severe anemia. A compromised immune system has been observed in patients with β-TM, whereas cytokines have a major role in immune modulation. Interleukin-4 (IL-4), IL-8, IL-13 and transforming growth factor-β (TGF-β) are critical in initiating pro-inflammatory responses, and the serum levels of those cytokines may be involved in the pathophysiology of β-thalassemia (β-thal). To assess this hypothesis, we studied 23 pediatric patients with β-TM by measuring serum levels of IL-4, IL-8, IL-13 and TGF-β, as well as evaluating infection frequency per year, total number of transfusions and serum ferritin (SF) levels, together with age-matched healthy controls. We found that patients with β-thal had higher IL-8, IL-13 and TGF-β concentrations than normal controls, whereas markedly decreased serum IL-4 level was documented in patients with β-TM. Serum IL-4 level of β-thal patients showed a negative significant correlation with infection frequency, total number of transfusions and SF levels. On the contrary, serum levels of IL-8, IL-13 and TGF-β exerted a positive relationship with those clinical parameters. Taken together, our study implies that dysregulated cytokine profile might contribute to iron overloads and impair immune cell functions, thus serving as useful biomarkers for diagnosis and evaluation of β-TM in the future. Our study sheds new light on the pathogenesis of β-TM.